FORM OF COMMODIFICATION OF DECORATIVE VARIETY OF GAYO SKIN MOTIF IN KEBAYAKAN DISTRICT, ACEH CENTRAL REGENCY - Rita Fitri; Ibnu Hajar; Nurjannah Nurjannah (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2021)
The study is intended to determine how the form of commodification variety of Kerawang Gayo decorative motifs in the Kebayakan District of Central Aceh Regency. This research is carried out through research qualitative with descriptive approach. The informant of the research is determined by purposive sampling technique to involve leaders of indigenous, artisans of Kerawang Gayo and designers. Data collection techniques were carried out through in-depth interviews, participatory observation and documentation. The result of the research shows that commodification is a process that is not only related to how products are becoming the product of mass, but it also relates to how a product that can be distributed to the market to meet the needs of consumers. The form of commodification variety of decorative motifs filigree Gayo is not only poured on the walls of the house indigenous Gayo, but it has been modified in some form of products such as upuh ulen-ulen, fashion custom wedding, bags, caps and other souvenirs. The motifs that are used in the form of commodification filigree Gayo consist of five motif bases that is emun berangkat, pucuk rebung, puter tali, tapak seleman, dan peger. Thus, the commodification is becoming very important in preserving the art of culture, both for the benefit of sustainability as well as the increase in business that motif used still maintained its continuity and become the identity of the tribe Gayo that in the call with Kerawang Gayo.